Assessment of Cd(II) adsorption capability and mechanism from aqueous phase using virgin and calcined lignin. Issue 6 (June 2020) - Ogata, Fumihiko; Nagahashi, Eri; Miki, Hirona; Saenjum, Chalermpong; Nakamura, Takehiro; Kawasaki, Naohito
Abstract: Herein, to assess the adsorption capability and elucidate the adsorption mechanism of Cd(II) from the aqueous phase, virgin lignin (Lig) and calcined lignin (Lig200, Lig400, Lig600, Lig800, and Lig1000) were prepared. The characteristics, including specific surface area and pore volume of adsorbents, were investigated, and the adsorption capability along with the effect of temperature, contact time, and pH on the adsorption of Cd(II) were evaluated. The characteristics of the adsorbent surface were related to the adsorption capability of Cd(II) from the aqueous phase, and the correlation coefficients between the adsorbed amount and specific surface area and total pore volumes were 0.872 and 0.960, respectively. Moreover, the amount adsorbed using Lig800 (91.3 mg/g) was higher than that using other adsorbent samples. The adsorption mechanism was elucidated to investigate the binding energy and elemental distribution before and after Cd(II) adsorption. Finally, the desorption capability of Cd(II) from Lig800 using a hydrochloric acid solution was demonstrated. Results obtained herein suggest that Lig800 is a potential candidate for the removal of Cd(II). Abstract : adsorption; Cadmium ion; Calcination; Lignin; Bioengineering; Surface Chemistry; Environmental Chemistry; Environmental Engineering; Environmental Pollution; Chemistry; Environmental science.